PENGEMBANGAN MODEL PEMBELAJARAN INKUIRI SOSIAL PADA PEMBELAJARAN KETERAMPILAN MENULIS PUISI YANG BERMUATAN NILAI-NILAI PENDIDIKAN KARAKTER PADA PESERTA DIDIK KELAS VIII SMP - Febriasari, Diani (Widya Warta, 2014)
The purposes of this study were to search (1) the need for the development of social inquiry model in character education values-contained learning of poetry writing skill in the 8thyear-students of junior high school and (2) the principles of the development of social inquiry model in character education values-contained learning of poetry writing skill in the 8thyear-students of junior high school. The research was conducted by making use of design research and development. The data collecting instruments applied were observation sheets,questionnaires, interviews, tests, and documentation. While, the data were analyzed using descriptive qualitative method. The results showed that (1) teachers need a comprehensivepoetry writing material containing character education, the use of social model inquiry which enables the students to find the answers themselves, under teachers’ guidance, and with theuse of pictorial media to trigger students’ imagination. Students need some attractive and easy poetry writing materials, a vivid procedure of poetry writing learning, the use of pictorial media to develop students’ ideas, a guidance in developing ideas, examples of responsible behavior, discipline, and curiosity and (2) the social inquiry model was oriented to intellectual development, principles of interaction, principles of questioning, principles of thinking, and principles of openness.